Aktivitas Mendengarkan Program Substereobdg Radio Oz 103.1 Fm Bandung untuk Mendapatkan Kepuasan Pendengar - Akmal Azhar Haikal; Endri Listiani (UNISBA Press, 2022)
Abstract. The development of technology is currently growing rapidly, especially in the field of information can provide a benefit and satisfaction for users to find and obtain the desired information through the media, one of which is radio. Radio listeners will usually be selective in choosing radio broadcasts according to what they like, it is driven by certain need motives based on what listeners want to consume radio broadcasts. Broadcast programs are the product of every radio station that must provide satisfaction for the listeners to keep listening to the broadcast program. Oz Radio Bandung is one of the private youth radios that has interesting broadcast programs including the Substereobdg. This research was conducted to determine the level of listener satisfaction using the Uses & Gratifications. With the title